1990
DOI: 10.3354/meps068137
|View full text |Cite
|
Sign up to set email alerts
|

Juncus roemerianus production and decomposition along gradients of salinity and hydroperiod

Abstract: Juncus roemerianus Scheele, the black needlerush, dominates much of an irregularly flooded salt marsh at the Cedar Island National Wildhfe Refuge, North Carolina, USA. We examined its dynamics of growth, senescence, and decomposition along a 1.6 km transect into the marsh over salinity and hydroperiod gradients passing successively through 3 distinct vegetational zones. Little difference was noted among zones in any of the dynamic aspects examined. Aerial, annual net primary production of J. roernerianus avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…One explanation for this result would be that nitrogen was used for biomass production when conditions favored rapid growth, but accumulated in tissues if any factor other than nitrogen availability limited growth. This effect would be more likely to occur for Spartina than for Juncus because Spartina has a guerilla morphology (Harper 1977) and is capable of rapid growth under favorable conditions, whereas Juncus has a phalanx morphology, conserves nutrients (Kruczynski et al 1978;Christian et al 1990) and is less capable of rapid growth.…”
Section: Plant Nitrogen Contentmentioning
confidence: 99%
“…One explanation for this result would be that nitrogen was used for biomass production when conditions favored rapid growth, but accumulated in tissues if any factor other than nitrogen availability limited growth. This effect would be more likely to occur for Spartina than for Juncus because Spartina has a guerilla morphology (Harper 1977) and is capable of rapid growth under favorable conditions, whereas Juncus has a phalanx morphology, conserves nutrients (Kruczynski et al 1978;Christian et al 1990) and is less capable of rapid growth.…”
Section: Plant Nitrogen Contentmentioning
confidence: 99%
“…In the case of emergent macrophytes, abscission and collapse of shoot material to the sediment surface does not occur immediately following shoot senescence and death. This results in the accumulation of standing dead plant litter (Christian et al 1990;Findlay et al 1990;Wetzel and Howe 1999), which undergoes considerable initial microbial decay prior to its collapse into the aquatic environment (Newell 1993(Newell , 1996Bärlocher and Biddiscombe 1996;Kuehn and Suberkropp 1998a,b;Kuehn et al 1998Kuehn et al , 1999. Newell et al (1995), by using methods to assess rates of fungal biomass production (Newell and Fallon 1991;Gessner and Newell 1997), reported that microbial biomass and production associated with naturally standing and fallen litter of the freshwater sedge, Carex walteriana, was dominated by fungal decomposers, with bacterial biomass and production increasing only slightly after standing litter fell to the sediment surface.…”
mentioning
confidence: 99%
“…Large amounts of standing dead plant material can accun~ulate in wetlands, and at certain times of the year may exceed the above ground mass of living plant matter (Jordan & Whigham 1988, Christian et al 1990, Lee 1990. Diverse fungal assen~blages have been identified from standing dead litter of both freshwater and salt marsh emergent macrophytes (e.g.…”
Section: Introductionmentioning
confidence: 99%